Rapid expansion of academic upper secondary graduation in Germany—Changing social inequalities in the transition to secondary and to tertiary education?. (April 2023) - Scharf, Jan; Becker, Michael; Neumann, Marko; Maaz, Kai
Abstract: Taking as its point of departure the rapid expansion in the proportion of students graduating with a university entrance diploma ( Abitur ) in Germany, this paper adds to research on the mechanisms and effects of academic educational expansion, a worldwide phenomenon in the 20th and 21st century. Drawing on Boudon's theory of primary and secondary effects of social origin, we seek to understand if the educational expansion went along with a decreasing or persisting role of social background. Therefore, we analyze educational inequalities in two respects: first, in the transition from primary school to the academic track ( Gymnasium ) leading to the Abitur and, second, in the transition to tertiary education after academic upper secondary education. The study is based on two student cohorts (initial N  = 13, 026 and N  = 13, 873) who obtained university entrance diplomas in 2005 (cohort 1) and 2011/2012 (cohort 2) in the school system of the federal state of Hamburg (Germany). These cohorts were assessed during secondary education between 1996 (start of cohort 1) and 2012 (end of cohort 2). Employing the KHB decomposition method, we break the total effect of social background down into the relative importance of achievement differentials (primary effects) and educational decisions (secondary effects). Our findings indicate no changes in the total effects of social background and thus suggest that educational inequalities related to social origin persisted in both of the transitions we studied. However, when comparing both cohorts, we noted a clear decrease in secondary effects regarding transitions to the academic secondary track, meaning that achievement-related social differences gained in importance compared to the period before the educational expansion. At the same time, we observed a slight increase in the relative importance of secondary effects for transitions to tertiary education during the expansion. As a further result, our study shows that the rapid expansion of academic upper secondary graduation is mainly the consequence of an increase in the number of Abitur graduates via alternative paths besides the Gymnasium .